Perancangan Aplikasi Kompresi File Dokumen Menggunakan Algoritma Adiitive Code - Tanjung, Rizki Yanur; Mesran, Mesran (STMIK Budi Darma, 2021)
Along with the development of technology today, data has a very important role. Sophisticated technological developments have resulted in a large amount of digital data stored in a storage medium. Moreover, if the data continues to be stored for an indefinite period of time until it reaches the maximum storage limit, the storage media will be full and cannot store other data. Data can be text, images, audio or even video. Data often has a very large size. For that we need a technique to change the size of the data to make it smaller. This technique is called compression or better known as data compression. Data compression is a process of converting a set of data into a coded form to save the need for data storage space. On this basis, the Design of a Document File Compression Application Using the Additive Code Algorithm is made so that it can help computer users to compress document files that were originally large to their smallest size